Design, Structure Activity Relationships and X-Ray Co-Crystallography of Non-Steroidal LXR Agonists - Edwards, A. S.; Bennett, D. J.; Carswell, E. L.; Cooke, A. J.; Nimz, O. (Current Medicinal Chemistry, 2008)
The Liver X Receptor (LXR) α and β isoforms are members of the type II nuclear receptor family which function as a heterodimer with the Retinoid X Receptor (RXR). Upon agonist binding, the formation of the LXR/RXR heterodimer takes place and ultimately the regulation of a number of genes begins. The LXR isoforms share 77% sequence homology, with LXRβ having highest expression in liver, intestine, adipose tissue, and macrophages and LXRα being ubiquitously expressed. The aim of this article is to review the reported medicinal chemistry strategies towards the optimisation of novel non-steroidal chemotypes as LXR agonists. An analysis of the structural features important for LXR ligand binding will be given, utilising both structural activity relationship data obtained from LXR assays as well as X-ray co-crystallographic data obtained with LXR ligands and the LXR ligand binding domain (LBD). The X-ray co-crystallographic data analysis will detail the key structural interactions required for LXR binding/agonist activity and reveal the differences observed between chemotype classes. It has been postulated that a LXRβ selective compound may have a beneficial outcome on the lipid profile for a ligand by dissociating the favourable and unfavourable effects of LXR agonists. Whilst there have been a few examples of compounds showing a modest level of LXRα selectivity, obtaining a potent LXRβ selective compound has been more challenging. Analysis of the SAR and X-ray cocrystallographic data suggests that the rational design of a LXRβ selective compound will not be trivial.
Keywords: Liver X Receptor (LXR)